Processing and properties of aligned multi-walled carbon nanotube/aluminoborosilicate glass composites made by sol-gel processing - Otieno, G; Koos, A; Dillon, F; Wallwork, A; Grobert, N; Todd, R (Elsevier, 2010)
We describe a novel sol-based approach for producing aluminoborosilicate glass composites containing continuous, aligned carbon nanotubes. The process involves the production of aligned carbon nanotubes (ACNT) via aerosol chemical vapour desposition (CVD), followed by infiltration of the ACNT with aluminoborosilicate sol. The advantages of this process are three fold: (1) aerosol CVD is an efficient method of producing clean, aligned arrays of CNTS, (2) sol-gel chemistry provides a simple route to infiltration of the ACNTs, and (3) carbon nanotube (CNT) agglomeration problems associated with CNT composites are circumvented. ACNTs (carpets) with heights of up to 4.4 mm were grown with areas of 10 mm x 20 mm for composite fabrication. The composite showed extensive pull-out of the CNTs on a fracture surface and improved thermal and electrical conductivities of 16 Wm⁻¹K⁻¹ and 5-8 x 10² Sm⁻¹ respectively compared with only 1.2 Wm⁻¹K⁻¹ and 10⁻¹³Sm⁻¹ for the monolithic glass.